Mathematics : a second start - Page, S. G.; Berry, J. S. (John Stephen), 1947-; Hampson, H. (Howard); ScienceDirect eBooks (Chichester, England. : Horwood Pub., 2002)
Provides less mathematically minded students with a gentle introduction to basic mathematics and some more advanced topics. Covering algebra, trigonometry, calculus and statistics, it manages to combine clarity of presentation with liveliness of style and sympathy for students' needs. It is straightforward, pragmatic and packed full of illustrative examples, exercises and self-test questions. The essentials of formal mathematics are lucidly explained, with terms such as 'integral' or 'differential equation' fully clarified. Provides a gentle introduction to basic mathematics and some more advanced topicsSystematically covers algebra, trigonometry, calculus and statisticsContains illustrative examples, exercises and self-test questions.
TRIGONOMETRIC RATIOS FOR ANGLES OF ANY MAGNITUDETRIGONOMETRIC RATIOS WHEN OP LIES ON THE AXES; THE ASSOCIATED ACUTE ANGLE; USE OF CALCULATORS; GRAPHS OF THE TRIGONOMETRIC RATIOS; TO FIND ALL THE ANGLES WITH A GIVEN SIN, COS OR TAN; THE MINOR RATIOS; GRAPHS; USE OF CALCULATOR WITH THE MINOR RATIOS; THE THEOREM OF PYTHAGORAS; Chapter 18. Calculus of Trigonometry; RADIANS: A NEW WAY OF MEASURING ANGLES; THE ADDITION FORMULAE; SMALL ANGLES; DIFFERENTIATION OF TRIGONOMETRIC FUNCTIONS; Chapter 19. The Law of Natural Growth; COMPOUND INTEREST; DIFFERENTIATION AND INTEGRATION OF THE FUNCTION y = ex.
Originally published in 1986 by Ellis Horwood Limited.
Includes index.
Print version record.
Elsevier
Keywords: Mathematics; MATHEMATICS -- Essays; MATHEMATICS -- Pre-Calculus.; MATHEMATICS -- Reference; Mathematics; Electronic books